Antioxidant effects of alpha-, gamma- and succinate-tocopherols in guinea pig retina during ischemia-reperfusion injury - Aydemir, Orhan; Naziro?lu, Mustafa; Çelebi, Serdal; Yilmaz, Turgut; Kükner, A. Şahap (My University, 2004)
The purpose of this study is to investigate the efficacy of alpha-tocopherol (AT), gamma-tocopherol (GT) and d-alpha-tocopherol polyethylene glycol 1000 succinate (TPGS) in preventing the retinal injury followed by ischemia-reperfusion (IR). The eyes of 40 adult male guinea pigs were used in the study. The guinea pigs were divided into five groups of eight rats each. First and second groups were used as control and IR groups, respectively. Third, fourth and fifth groups received subcutaneously AT, GT and TPGS, respectively. Treatment with each vitamin was performed before 5 min of ischemia with reperfusion at 6 h intervals for three times. Retinal ischemia was induced for 90 min, then followed by reperfusion for 24 h. The animals were killed at 24 h of reperfusion. Lipid peroxidation (LP) and glutathione (GSH) levels were measured in right retinas by using a spectrofluorometer. Retinal GSH levels were found significantly lower (p < 0.002) in the IR group than in control group and there was a significant increase in the LP levels in IR group (p < 0.001). The decrease of GSH and increase of LP levels in the IR animals were significantly (p < 0.05 and 0.001) improved by the administration of the Vitamin E forms. When compared to GT group, there were no significant differences in LP levels in AT and TPGS groups. However, LP level in AT group was significantly (p < 0.01) lower than in the TPGS group. The GSH levels were higher (p < 0.001) in AT and TPGS groups than in IR group. Therefore, modulator effect of AT and GT were greater than that of TPGS. In conclusion, present data demonstrate that there is an increase in the LP in the retina of IR-induced animals and a decrease in the GSH levels. However, subcutaneous AT, GT and TPGS were effective in preventing retinal injury followed by ischemia-reperfusion. The subcutaneous AT may play a role in treating IR injury. © 2004 Elsevier Ireland Ltd. All rights reserved.
Keywords: Alpha-tocopherol; d-Alpha-tocopherol polyethylene glycol 1000 succinate; Gamma-tocopherol; Glutathione; Ischemia-reperfusion injury; Retina